2020
DOI: 10.1007/s10096-020-03882-z
|View full text |Cite
|
Sign up to set email alerts
|

Drugs with new lease of life as quorum sensing inhibitors: for combating MDR Acinetobacter baumannii infections

Abstract: The emergence of multidrug-resistant (MDR) strains is a major health problem worldwide. There is an urgent need for novel strategies to combat bacterial infections caused by MDR strains like Pseudomonas aeruginosa and Acinetobacter baumannii. Quorum sensing (QS) is a critical communication system in bacterial community controlling survival and virulence. The awareness of the importance of QS in bacterial infections has stimulated research to identify QS inhibitors (QSIs) to defeat microbes. In this study, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 82 publications
2
25
0
Order By: Relevance
“…These findings are consistent with the fact that XDRAB has been increasingly isolated in clinical settings globally, which calls for combination therapy 11 . Indeed, the clinical choice of antibacterial drugs for XDRAB infections is limited, and the new therapeutic regime with combination drug use has been pursued 16,17,20,21 . Given that biofilms contribute to bacterial virulence and resistance 22 , we targeted agents with anti-biofilm property for their potential in combination drug use against A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with the fact that XDRAB has been increasingly isolated in clinical settings globally, which calls for combination therapy 11 . Indeed, the clinical choice of antibacterial drugs for XDRAB infections is limited, and the new therapeutic regime with combination drug use has been pursued 16,17,20,21 . Given that biofilms contribute to bacterial virulence and resistance 22 , we targeted agents with anti-biofilm property for their potential in combination drug use against A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
“…Based on literature information [12][13][14][15][16][17] , we have identified a range of metal salts, biocides and conventionally used antibiotics with ability to affect bacterial biofilm formation. However, no or little data were specifically available to A. baumannii.…”
Section: Sub-inhibitory Concentrations Of the Biofilm Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, Raorane et al (2019) investigated the antibiofilm activities of 12 flavonoids and showed that curcumin and other flavonoids have the potential to control biofilm formation and virulence in A. baumannii . Similarly, according to the latest research report, four FDA-approved drugs (erythromycin, levamisole, chloroquine, and propranolol) were studied for the first time as inhibitors for QS against clinical A. baumannii ( Seleem et al, 2020 ). This study showed that antibiotics like erythromycin not only had antibacterial activity but also inhibited the formation of biofilm induced by QS.…”
Section: Mechanism Of Quorum Sensing In Acinetobacter Baumamentioning
confidence: 99%
“…Exotoxin pyocyanin is one of the major virulence factors secreted by P. aeruginosa . Pyocyanin is regulated by the quorum sensing (QS) system, an important communication system that controls survival, virulence and biofilm formation in bacterial communities (Seleem et al, 2020 ). The QS system is mainly regulated by four QS network sub-systems, including the las, rhl , PQS, and IQS systems.…”
Section: Introductionmentioning
confidence: 99%